Harmonizing Regional Competition Laws and Policies: A Way Forward for ASEAN Economic Growth - Fathari, Muhammad Reza; Efendy, Andi Rifky Maulana (Indonesian Comparative Law Review, 2023)
The prominent subject of discussion within the context of the ASEAN Economic Community is the harmonization of competition law in the region (AEC). In order to remove and reduce potential barriers to economic activity, ASEAN has adopted free trade through economic integration among its member nations. This study aims to examine why it is crucial to harmonize ASEAN competition law and to determine what the ASEAN business competition law harmonization model looks like. This paper used normative method with utilizing a statutory and a comparative approach which are presented descriptively. The results demonstrated that legal system conflicts can be addressed and legal disparities can be lessened by initiatives at harmonization. To do this, ASEAN must at the very least harmonize three key aspects of ASEAN Member States' competition laws: the substance of the law, law enforcement, and competition commission. In this context, collaboration amongst competition enforcement agencies can be used to implement the ASEAN model of harmonising competition legislation. Cooperation can take the form of notification, information sharing, enforcement cooperation between commissions, consultation, and conciliation.